Digital marketing strategy in promoting product - Christina, Imelda Debby; Fenni, Fenni; Roselina, Devia (Management and Entrepreneurship: Trends of Development, 2019)
A rapid internet development and its function has become one of the most important technologies in the world since it is very influential for human life. Considering this, one of the paid television companies makes an integrated marketing communication using internet as a tool for promoting its product. This study aims to know the role and strategy of various digital marketing channels, including website, search engine marketing (SEM), online PR, display advertising, email marketing and social media marketing in promoting product. The methodology is descriptive qualitative using interview and participant observation. The data were collected through documents and literature which related to digital marketing. This study found that digital marketing strategy has important role in promoting product. The whole digital marketing strategy, either in its planning, implementation, or evaluation, has its own uniqueness. It showed that digital marketing strategy has been run well within the company. JEL Classification: M31, M37, M39.